PEMBUATAN PESTISIDA NABATI DAUN PEPAYA DI DESA TANJUNG ALAM KECAMATAN SEI DADAP KABUPATEN ASAHAN - Handayani, Turi; Fajri, Surya; Satria, Indra; Syahputra, Imam; Fadillah, Chika Intan (Smart Education, 2025)
Abstract: Agriculture is a key sector supporting food security and the community's economy. One of the obstacles in agricultural activities is pest attacks, which are generally addressed with the use of chemical pesticides. However, excessive use of chemical pesticides can have negative impacts on human health and the environment. Therefore, alternative solutions are needed in the form of safer and more environmentally friendly botanical pesticides. This community service activity was carried out in Tanjung Alam Village through socialization of the manufacture of botanical pesticides from papaya leaves to students of SMP IT Adabiyah. The activity methods included counseling, a question and answer session, and hands-on practice in making botanical pesticides. The results of the activity showed that students understood the dangers of chemical pesticides and learned how to make botanical pesticides from simple ingredients easily found in the surrounding environment. This program is expected to increase environmental awareness, reduce dependence on chemical pesticides, and support the creation of sustainable agriculture in the community. Keywords: papaya leaves, socialization, botanical pesticides, socialization Abstrak: Pertanian merupakan sektor utama yang mendukung ketahanan pangan dan perekonomian masyarakat. Salah satu kendala dalam aktivitas pertanian adalah serangan hama yang umumnya diatasi dengan penggunaan pestisida kimia. Namun, pemakaian pestisida kimia secara berlebihan dapat menimbulkan dampak negatif bagi kesehatan manusia dan lingkungan. Oleh karena itu, diperlukan solusi alternatif berupa pestisida nabati yang lebih aman dan ramah lingkungan. Kegiatan pengabdian masyarakat ini dilaksanakan di Desa Tanjung Alam melalui sosialisasi pembuatan pestisida nabati berbahan dasar daun pepaya kepada siswa SMP IT Adabiyah. Metode kegiatan meliputi penyuluhan, sesi tanya jawab, serta praktik langsung pembuatan pestisida nabati. Hasil kegiatan menunjukkan bahwa siswa memahami bahaya pestisida kimia dan mengetahui cara pembuatan pestisida nabati dengan bahan sederhana yang mudah ditemukan di sekitar lingkungan. Program ini diharapkan dapat meningkatkan kesadaran lingkungan, mengurangi ketergantungan terhadap pestisida kimia, serta mendukung terciptanya pertanian berkelanjutan di masyarakat. Keywords: daun pepaya, sosialisasi, pestisida nabati, sosialisasi